Beyond binary: exploring the interplay of China’s digital transformation and firm performance through dual mechanism analysis - Chen, Shunru; Alexiou, Constantinos; Lee, Seungrae (Taylor & Francis, 2024)
Utilizing data from Chinese A-share listed firms we explore the paradoxical effects of digital transformation on firms’ financial and operational performance. Through text mining, mechanism and heterogeneity analyses, the study’s findings indicate that digital transformation may inflate operational costs and compromise firm performance. When considering financial restrictions and R&D, the productivity gains emanating from digital transformation, underscores the symbiotic potential of concurrent technological and financial strategies. Heterogeneity analyses reveal a differentiated impact: larger firms and specific sectors, such as technology, witness a significant boost in productivity, whereas state-owned entities and joint ventures are less susceptible to performance downturns.
Keywords: Business & Management; 3505 Human resources and industrial relations; 3507 Strategy, management and organisational behaviour; China; dual mechanisms; digital transformation; firm performance; text mining